2008
DOI: 10.1002/jbm.a.32331
|View full text |Cite
|
Sign up to set email alerts
|

Polar surface chemistry of nanofibrous polyurethane scaffold affects annulus fibrosus cell attachment and early matrix accumulation

Abstract: Regeneration of the annulus fibrosus (AF), one of the three components of the intervertebral disc (IVD), is challenging because of the tissue complexity and our limited knowledge about AF cell biology. The purpose of this study was to determine if modulating surface chemistry of polycarbonate polyurethane (PU) scaffolds would influence annulus fibrosus cell adhesion and early tissue formation. To vary surface energy, a novel anionic dihydroxyl oligomer (ADO) was synthesized and incorporated into the PU base po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 71 publications
0
60
0
Order By: Relevance
“…Nerurkar et al [35][36][37] have assessed the mechanics of aligned poly-(e-caprolactone) scaffolds and their ability to induce alignment in AF cells and tissue. The high surface to volume ratio of these scaffolds is also expected to favor cell attachment and retention of cell phenotype [33,38]. The purpose of this study was to characterize a biodegradable electrospun PU nanofiber biomaterial and determine its suitability for use in repairing the AF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nerurkar et al [35][36][37] have assessed the mechanics of aligned poly-(e-caprolactone) scaffolds and their ability to induce alignment in AF cells and tissue. The high surface to volume ratio of these scaffolds is also expected to favor cell attachment and retention of cell phenotype [33,38]. The purpose of this study was to characterize a biodegradable electrospun PU nanofiber biomaterial and determine its suitability for use in repairing the AF.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that a degradable polycarbonate urethane (PU) previously reported in Ref. [32] could be processed, with the addition of anionic dihydroxyl oligomers (ADO), which enhance cell attachment [33], using electrospinning applications to fabricate aligned fibers. These structures mimic the aligned nature of the AF, and thus provide an appropriate scaffold to support the growth of such a tissue.…”
Section: Introductionmentioning
confidence: 99%
“…PU nanofibrous scaffolds in the absence or presence of different amounts of ADO were similar in appearance. Increasing the material surface's polar character of the scaffolds resulted in a positive enhancement of AF cell attachment [95]. Both the tensile strength and initial modulus of aligned scaffolds were higher than the random fiber scaffold.…”
Section: Single Unit With Oriented Fibermentioning
confidence: 96%
“…The mechanical tests revealed that POM has an excellent deformability: the compressive stress, young's modulus, and tensile strength markedly increased as the polymerization time increased. There was no permanent deformation after 500 press-loading and release cycles with Poly-D-L-lactide/Bioglass [90,91] Silk [92,93] Genipin crosslinked fibrin [94] Single unit with fiber orientation Aligned alginate/chitosan [88] Polycarbonate polyurethane linked with dihydroxyl oligomer [95,96] Polycaprolactone [97,98] Poly-L-Lactide [99] Silk fibers/chondroitin sulphate [100] Collagen fibrils [101] Biphasic scaffold Poly (polycaprolactone triol malate)/DBM [102] Composite scaffold Poly-L-Lactide as AF and hyaluronic acid hydrogel as NP [24] Polyglycolic Acid/poly-l-lactic as AF and alginate hydrogel as NP [103] Silk scaffold as AF and silicon as NP or hyaluronic acid as NP [104,105] 30 % maximum strain. When implanted into mice back subcutaneous pocket, there were no inflammation responses were found [89].…”
Section: Single Unit Without Fiber Orientationmentioning
confidence: 99%
“…Some research groups have considered electrospinning as a powerful technique to manufacture scaffolds for annulus tissue engineering [124,[133][134][135]. The basic idea was that the electrospun fibers can closely reproduce the scale of collagen fibers present in most soft tissues, whilst the collection onto a rotating mandrel may provide an aligned mesh consisting of nanofibers.…”
Section: Intervertebral Disc: From Repair To Regenerationmentioning
confidence: 99%